Penggunaan Matriks SWOT dan QSPM dalam Menentukan Strategi Pengembangan Kompetensi Karyawan PT. Ketapang Subur Lestari - Sri Wahyunawati (Yayasan Literasi Sains Indonesia, 2023)
The development of human resources for oil palm plantations has a strategic role considering the demand for palm oil derivative products continues to increase both domestically and abroad. Qualified human resources are needed to be able to meet the high demand, including competence, professionalism, skills, independence, knowledge and competitiveness. The aim of the research is to analyze internal and external factors and develop appropriate human resource development strategies. The analytical tools used are the IFAS Matrix (Internal Factors Analysis Summary), the EFAS Matrix (External Factors Analysis Summary), the IE Matrix (Internal External Matrix), the SWOT Matrix and the QSPM Matrix (Quantitative Strategic Planning Matrix). IE Matrix Analysis of the competency of PT KSL's employees is in quadrant V, namely in an average or moderate position, with a Hold and Maintain strategy. The chosen strategy for PT KSL's employee competency development is training and development with the aim of improving and developing employee competencies to improve company performance and profits. Analysis of the QSPM matrix yields a dominant value of TAS 7.712, namely utilizing training centers, utilizing government support, and always following oil palm business trends so that employees have good competence to increase company production and productivity.